Apoptosis of Limb Innervating Motor Neurons and Erosion of Motor Pool Identity upon Lineage Specific Dicer Inactivation - Chen, Jun-An; Wichterle, Hynek (Frontiers in Neuroscience, 2012)
Diversification of mammalian spinal motor neurons into hundreds of subtypes is critical for the maintenance of body posture and coordination of complex movements. Motor neuron differentiation is controlled by extrinsic signals that regulate intrinsic genetic programs specifying and consolidating motor neuron subtype identity. While transcription factors (TFs) have been recognized as principal regulators of the intrinsic program, the role of posttranscriptional regulations has not been systematically tested. MicroRNAs produced by Dicer mediated cleavage of RNA hairpins contribute to gene regulation by posttranscriptional silencing. Here we used Olig2-cre conditional deletion of Dicer gene in motor neuron progenitors to examine effects of miRNA biogenesis disruption on postmitotic spinal motor neurons. We report that despite the initial increase in the number of motor neuron progenitors, disruption of Dicer function results in a loss of many limb- and sympathetic ganglia- innervating spinal motor neurons. Furthermore, it leads to defects in motor pool identity specification. Thus, our results indicate that miRNAs are an integral part of the genetic program controlling motor neuron survival and acquisition of subtype specific properties.